Mitigating negative livelihood impacts of no-take MPAs on small-scale fishers. (May 2020) - Mizrahi, Me'ira; Duce, Stephanie; Khine, Zin Lin; MacKeracher, Tracy; Maung, Khin May Chit; Phyu, Ei Thal; Pressey, Robert L.; Simpfendorfer, Colin; Diedrich, Amy
Abstract: Marine Protected Areas (MPAs) have the potential to support small-scale fishers in managing their resources. However, a general failure to consider the varying levels of vulnerability of fishers has resulted in MPAs that, often unintentionally, adversely impact small-scale fishers. Furthermore, when fishers lack the capacity to adapt to MPA-related changes, MPAs may fail to meet conservation objectives because fishers do not comply with MPA regulations. In this study, we developed a systematic method to identify individuals who are most vulnerable to being negatively impacted by no-take MPAs through an index that represents individual-level vulnerability. We designed a method for identifying these individuals based on four socioeconomic factors pertaining to vulnerability to MPA changes: livelihood diversity, education, age and wealth, then applied this method in two socially and economically heterogeneous communities in Myanmar's Myeik Archipelago. We used empirical data collected from 80 small-scale fishers in this area to represent each factor, then generated a local-level 'Livelihood Impact Potential Index' (LIPI) that reflects the degree to which a no-take MPA would impact an individual fisher's ability to support his or her livelihood. When attributed to each fisher's most frequented fishing ground, the LIPI can identify locations where no-take MPAs would be most detrimental to small-scale fishers' livelihoods based on their levels of vulnerability. The LIPI can thus be used alongside ecological and commercial fishing data to support planners in designing local-scale MPAs that maximise positive impact on biodiversity and minimise adverse impacts on the most vulnerable fishers in a community. Highlights: MPAs often adversely impact fishers if local level vulnerability is not considered. Linking level of vulnerability to a fishing grounds supports conservation planning. Fishers with high vulnerability should be supported if their grounds are restricted. Including vulnerability in MPA planning supports equity in fishing communities.